TRUE RESEARCH: CATALYST FOR CHANGE AND PROGRESS - Nierras, Mario C (PEOPLE: International Journal of Social Sciences, 2018)
Development is akin to progress. Societies which have the dream to progress focus on conducting and implementing researches which are responsive to development. Research and development are the inseparable partners to nation-building. It is believed and safer to say that the progress of a nation does not happen by sheer chance. It is the sustaining motivation and concentration on what to research plus the conscientious use of available and right resources that determine progress. Once research results are generated, concerned agencies need to assess which ones should be utilized or commercialized to propel growth and development. Conducting true research is oftentimes costly both financial and otherwise, but the results might also be overwhelmingly satisfying. Developing and instilling a culture of research to the citizenry is a good national agenda to every country. Since research is educative, education has to be research-oriented. People’s clamor for a better society may be answered partly or wholly through the conduct of true research. Indeed, if research will be taken sincerely and honestly, good or excellent outputs may be produced that could fuel development to proceed. It is a big challenge to all nations especially the developing and underdeveloped economies, to use their limited capital in pursuing a priority-based research agenda. Wise use of meager resources through genuine research is a real exponent of developmental change.